2011
DOI: 10.1109/ted.2011.2161992
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Band-Gap Opening on Ballistic Electron Transport in Bilayer Graphene and Graphene Nanoribbon FETs

Abstract: Although graphene is a zero-gap semiconductor, band-gap energies up to several hundreds millielectron volts have been introduced by utilizing quantum mechanical confinement in nanoribbon structures or symmetry breaking between two carbon layers in bilayer graphenes. However, the opening of a band-gap causes a significant reduction in carrier velocity due to the modulation of bandstructures in their low energy spectrums. In this paper, we study intrinsic effects of the band-gap opening on ballistic electron tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Since the presence of a band gap is a crucial property in electronic and/or optoelectronic devices, it is significant to introduce a band gap in graphene. This problem could be solved by doping, tailoring or controlling the dimensionality of graphene, which, however, usually result in crystallographic damage to the materials and unexpected loss in the excellent electrical properties. Therefore, it is important to find a solution that not only brings a tunable band gap but also reserves the integrity of graphene.…”
Section: Introductionmentioning
confidence: 99%
“…Since the presence of a band gap is a crucial property in electronic and/or optoelectronic devices, it is significant to introduce a band gap in graphene. This problem could be solved by doping, tailoring or controlling the dimensionality of graphene, which, however, usually result in crystallographic damage to the materials and unexpected loss in the excellent electrical properties. Therefore, it is important to find a solution that not only brings a tunable band gap but also reserves the integrity of graphene.…”
Section: Introductionmentioning
confidence: 99%
“…The high quality of Gr/hBN/BLG devices demonstrated in this work allows to readdress the broad field of possible applications offered by BLG, such as diodes [60], phonon-lasers [35,61], hot-electron bolometers [62], fieldeffect transistors (FET) [63][64][65] and tunnel FETs [66]. The latter two are especially interesting for terahertz (THz) detection, where graphene and BLG based devices have already shown promising results [67,68].…”
Section: Discussionmentioning
confidence: 98%
“…AGNRs have been theoretically predicted to have better carrier transport properties than BLG, n-channel Si MOSFETs and InPhigh-electron-mobility transistors (HEMTs) [122,123], particularly when they are used in GNRFETs with ribbon widths around 3-4 nm; however, recent studies have shown that thermal conductivity decreases around three orders of magnitude in GNRs with widths smaller than 10 nm, indicating a direct relation between the width of the GNR and its diffusive thermal conductivity and effective mean free path [124].…”
Section: Field-effect Devicesmentioning
confidence: 99%